Contextual Pedagogy Facilitates Literacy Acquisition For Junior High Slow Learners: Pedagogi Kontekstual Memfasilitasi Akuisisi Literasi Untuk Anak Lamban Belajar Sekolah Menengah Pertama - Mawir Mukhlish; Ikhlasul Ardi Nugroho (Academia Open, 2026)
General Background Reading ability functions as a fundamental competency supporting academic progression across all school subjects. Specific Background However, seventh-grade cohorts identified as slow learners at SMPN 1 Busang experience significant difficulties with word recognition, fluency, and text comprehension, which restricts their active classroom participation. Knowledge Gap Although literature documents the benefits of real-life learning connections, empirical research investigating its specific application for junior secondary slow learners within geographically remote rural environments remains limited. Aims This Classroom Action Research investigates the application of Contextual Teaching and Learning to develop the reading capabilities of seventh-grade slow learners. Results Following two interventional cycles utilizing familiar daily experiences and guided practice, student reading proficiency rates increased significantly from 30% to 90%, alongside mean score progressions from 58 to 78. The instructional adjustments also successfully stimulated active participation, word decoding accuracy, and the capacity to retell narratives. Novelty This study provides specific evidence that integrating familiar daily experiences with individualized pedagogical guidance directly accommodates the distinct cognitive requirements of junior high slow learners. Implications Educational institutions should adopt contextual pedagogical approaches and provide relevant visual resources to support inclusive literacy development in regular classrooms. Highlights Meaningful real-life learning connections successfully stimulate classroom motivation and text comprehension. Guided instructional methods significantly raise word decoding accuracy alongside narrative retelling capabilities. Iterative action research cycles demonstrate substantial test score progressions and academic success. Keywords Contextual Teaching And Learning; Classroom Action Research; Reading Skills; Slow Learners; Junior Secondary School